Acompanhamento das parcerias de desenvolvimento produtivo de produtos biológicos: proposta de revisão da resolução – RDC N° 02, de 2 de fevereiro de 2011 - Moreira, Marcelo Mario Matos (2019)
The Ordinance MS/GM n° 2.531/2014 was issued by the Ministry of Health to stablish the Public-private Sector Partnerships (PDP). It´s an initiative to orientate the Brazilian health industrial complex and biotech industries to increase the manufacturing of Strategic for the Unified Health System (SUS). These partnerships are celebrated between two or more public pharmaceutical companies and private pharmaceutical companies, to promote the local production. The monitoring of activities related to development, Good Manufacturing Practices (GMP) certification, license and post-license changes of the medicines is performed by a technical team of experts (CTR), composed by Anvisa´s, Ministry’s and public companies´ representatives responsible for submission of the PDP proposal. This dissertation aims to propose the Resolution´s update – RDC n° 2/2011 to include the procedures related to the GMP requirements and to align with the Ordinance MS/GM n° 2.531/2014. For this, it was performed a research related to PDP, recovered the GMP reports issued by Anvisa from January/2011 to December/2018 and joined the Ordinances and Resolutions regarding PDP. As a result, the findings of this study pointed that some of these companies with a PDP agreement need to reach an upper tech level, by getting knowledge, or professional and structural resources to start the manufacturing of Biosimilar Pharmaceuticals. The public industries can overcome this state with a CTR follow-up that help them to meet the GMP requirements, as approved in Resolution – RDC n° 17/2010. Finally, and regarding the needs to regulate the Anvisa´s participation in this follow up, this project propose as product, the review of the Resolution – RDC n° 2/2011, to support the PDP´s evolution according to the phase-by-phase established by the Ministry of Health.